Students’ Perceptions in Using Google Classroom as Online English Learning Platform - Pratika, Nine Dera; Kuswardani, Rahayu (RETAIN : Journal of Research in English Language Teaching, 2022)
Nowadays, distance learning has become an effective strategy in education to reduce the spread of Corona Virus. Google Classroom, a learning platform has become a preferable educational platform. This research investigates the students’ perceptions in using Google Classroom as an online English learning platform. It is limited towards the accessibility of using Google Classroom. The study uses a quantitative method and the questionnaires as the instrument using Likert scale given to 100 eleventh grade senior high school students in Gedangan, East Java who implement Google Classroom to learn English. The data analysis uses descriptive statistics by explaining the frequency, median and mode of the data. The result shows many students agree that Google Classroom is accessible and available on mobile phones. It has understandable features that makes students get clear learning instruction and know their learning progress and history. It helps them in submitting their assignments and it does not drain a lot of internet quota. However, they disagree about having good interaction, finding out which assignments have not been completed and saving their learning time. Meanwhile, they choose neutral for understandable learning material and non-paper usage, but a similar number choose neutral, agree and strongly agree for cheating possibility